Early Feeding Versus Delayed Feeding after Therapeutic Endoscopic Intervention in Upper GI Bleeding: : A Systematic Review and Meta-analysis (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Gastroenterology; Research